2017
DOI: 10.1186/s13256-017-1264-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis B virus infection with delayed appearance of hepatitis B core antibody in an immunocompromised patient: a case report

Abstract: BackgroundDespite the introduction of universal hepatitis B immunization programs worldwide, outbreaks of acute infection still occur in unimmunized individuals. A timely diagnosis of hepatitis B is necessary to ensure adequate clinical care and public health interventions that will reduce transmission. Yet, interpretation of hepatitis B serological markers can be complex. We present a case of hepatitis B with atypical markers, including delayed appearance of hepatitis B core antibody. Case presentationA 62-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Delayed or completely absent seroconversion in immunocompromised COVID-19 patients has been previously reported [ 11 ]. Delayed antibody responses to other virus-borne diseases such as Hepatitis B and West Nile has been shown in immunosuppressed patients [ 13 , 14 ]. Samples from these patients who were RT-PCR positive but IgG negative can be attributed to low levels of antibody production that were below the detection limits of the Architect™ and Panbio™ assays.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed or completely absent seroconversion in immunocompromised COVID-19 patients has been previously reported [ 11 ]. Delayed antibody responses to other virus-borne diseases such as Hepatitis B and West Nile has been shown in immunosuppressed patients [ 13 , 14 ]. Samples from these patients who were RT-PCR positive but IgG negative can be attributed to low levels of antibody production that were below the detection limits of the Architect™ and Panbio™ assays.…”
Section: Discussionmentioning
confidence: 99%
“…That patient developed anti-HBc 6 months after first positive HBsAg, with the delay attributed to immunosuppression due to Rituximab. Both Avettand-Fenoel et al and Brousseu et al showed that patients developed HBc antibodies once immunosuppression was less pronounced or after chemotherapy completion (16,17), further establishing the role of immune suppression in lack of anti-HBc response in acute HBV infection.…”
Section: Discussionmentioning
confidence: 94%
“…The patients in the study were immunosuppressed due to HIV infection, solid organ transplant (kidney, heart, or bone marrow), while 1 patient had HCV co-infection. More recently, Brousseu et al reported a case of acute HBV infection in a patient receiving rituximab for low-grade non-Hodgkin lymphoma with isolated HBsAg positivity (17).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we had few subjects with profound immunosuppression who were still negative 15 days after onset. We know, however, that seroconversion could occur later in such patients [ 18 , 19 ]. Future studies should focus on seroconversion from Day 15 to Day 30 in highly immunocompromised patients infected with COVID-19.…”
Section: Discussionmentioning
confidence: 99%